Policy Analysis of Central Java Governor Regulation Number 60 of 2019 Concerning Regional Poverty Alleviation Strategy of Central Java Province 2019-2023 Towards Poverty in Central Java Province - Koresy Wilma Pattiasina; Syofriza Syofyan; Agustina Suparyati (Dinasti Publisher, 2025)
This research aiming to analyze the Policy of the Governor of Central Java Regulation No. 60 of 2019 concerning the Regional Poverty Alleviation Strategy of Central Java Province for 2019-2023 on poverty in Central Java. The data of this study is secondary data sourced from the Central Statistics Agency of Central Java. The analysis methods used were descriptive statistics, data collection with random effect model (REM) and Class Typology with the number of objects in 35 districts / cities in Central Java Province. The results of the study revealed that simultaneously the dimensions of education, health, employment, basic infrastructure, food security and policy dummy had a significant impact with an adjusted r- square value of 0.364909 or 36.4% on poverty in Central Java. Partially, health indicators are life expectation, one of the basic infrastructure indicators, namely access to proper drinking water sources and dummy policies have a negative and significant effect on poverty. employment indicator, namely the open unemployment rate, has a positive and significant influence on poverty, while the education indicator, namely the pure participation rate of high school / equivalent, has a positive and insignificant influence on poverty and one of the indicators of basic infrastructure, namely proper sanitation and food security, namely the average calories consumption per capita, has a negative but not significant effect on poverty. The results of Classes typology analysis also revealed a number of districts / cities that have undergoing changes after the implementation of the policy.